Preparation, microstructure and rheological properties of asphalt sealants for bridge expansion joints. (15th February 2016) - Liu, Shuang; Mo, Liantong; Wang, Kai; Xie, Yanjun; Woldekidan, M.F.
Highlights: Asphalt sealants were modified by large amount of various modifiers. Network microstructure between polymer and bitumen was captured. Significant plateau region of master curves and black diagrams indicated improved rheology. Asphalt sealant's properties related well to mixture performance. Meso-scale finite element modelling was able to simulate the mixture response. Abstract: The service performance of asphaltic plug joints (APJs) is unsatisfactory. Premature cracking, rutting and debonding of APJ filling mixture is strongly related to the relevant properties of the used asphalt sealants. Better understanding on the sealant properties and their relation to the mixture performance is thus needed. In this paper, asphalt sealants were highly modified with a large amount of styrene–butadiene–styrene block copolymers (SBS), crumb rubber (CR), polypropylene (PP) and a combination of the above modifiers. Fluorescence microscopy analysis confirmed the formation of continuous polymer-rich phase, the swelling of crumb particle and the compatibility between the modifier and bitumen. Fundamental research into rheological behaviours was carried out by using viscosity test, dynamic modulus test, creep test and relaxation test. The significant plateau region of rheological master curves and black diagrams demonstrated an extraordinary effect of modification. Asphalt sealant's properties were found to well relate to APJ mixture performance. Finite element (FE) modelling at meso scale provided a favourable result and allowed bridging the gap between sealant properties and mixture performance. The provided test results could be used as a database for the selection and optimization of asphalt sealant.